NEW RECORDS FOR THE ICHTHYOFAUNA OF PUERTO VIEJO WETLAND (LIMA, PERU) - García-Pio, José Martín (2021)
Coastal wetlands are ecosystems with a high diversity of species, and they are considered of strategic importance in the conservation of biodiversity. Th e aim of this research is to record the ichthyofauna found in the wetlands of Puerto Viejo, Peru between November and December 2019. Passive fi shing gear was used through the use of mesh traps. Relative abundance was calculated by family and species, as well as alpha diversity indices: specifi c richness (S), Menhinick index (DMn), Shannon index (H’), and Simpson index (D). A total of 201 specimens were obtained belonging to fi ve genera and seven species: Bryconamericus peruanus (Muller & Troschel, 1845); Andinoacara stalsbergi Musilová, Schindler & Staeck, 2009; Amatitlania nigrofasciata (Günther, 1867); Oreochromis niloticus (Linnaeus, 1758), Poecilia reticulata Peters, 1859; Poecilia velifera (Regan, 1914); and Poecilia latipinna (Lesueur, 1821). Th e greatest diversity was found in Lagoon 1 (S = 4; H’ = 1,14; D = 0,65) and Lagoon 6 (S = 4; H’ = 1; D = 0,51). Bryconamericus peruanus, a native species for the Pacifi c Slope, accounted for more than 50% of collected specimens, followed by P. reticulata with 27.36% of total fi shes. A specimen of the endemic species A. stalsbergi was found; P. latipinna for Lima wetlands is reported. Despite strong anthropogenic pressure, the wetlands of Puerto Viejo retain a representative part of the continental ichthyofauna of the Peruvian coast.